Implementation of NUDT15 Genotyping to Prevent Azathioprine‐Induced Leukopenia for Patients With Autoimmune Disorders in Chinese Population. Issue 5 (22nd August 2022) - Wang, Chuang‐Wei; Chi, Min‐Hui; Tsai, Tsen‐Fang; Yu, Kuang‐Hui; Kao, Hsiao‐Wen; Chen, Hsiang‐Cheng; Chen, Chun‐Bing; Lu, Chun‐Wei; Chen, Wei‐Ti; Chang, Ya‐Ching; Chang, Chih‐Jung; Chang, Yun‐Ting; et al.
Abstract : Azathioprine (AZA) is commonly used for many autoimmune disorders; however, the limitation of its clinical use is due to potential toxicities, including severe leukopenia. Recent studies have identified genetic NUDT15 variants strongly associated with AZA‐induced leukopenia in Asian patients. This study aimed to investigate the strength of above genetic association and evaluate the usefulness of prospective screening of the NUDT15 variants to prevent AZA‐induced leukopenia in Chinese patients. AZA‐induced leukopenia in patients with autoimmune disorders were enrolled from multiple medical centers in Taiwan/China between 2012 and 2017 to determine the strength of genetic association of NUDT15 or TPMT variants by whole exome sequencing (WES). Furthermore, a prospective study was conducted between 2018 and 2021 to investigate the incidence of AZA‐induced leukopenia with and without genetic screening. The WES result showed the genetic variants of NUDT15 R139C ( rs116855232 ) ( P  = 3.7 × 10 −25, odds ratio (OR) = 21.7, 95% confidence interval (95% CI) = 12.1–38.8) and NUDT15 rs746071566 ( P  = 4.2 × 10 −9, OR = 7.1, 95% CI = 3.7–13.7), but not TPMT, were associated with AZA‐induced leukopenia and NUDT15 R139C variant shows the highest sensitivity with 92.5%. Furthermore, the targeted screening of 1, 013 participants for NUDT15 R139C enabled those identified as carriers to use alternative immunosuppressants. This strategy resulted in a significant decrease in the incidence of AZA‐induced leukopenia compared with historical incidence (incidence rate = from 7.6% decreased to 0.4%; P  = 9.3 × 10 −20 ). In conclusion, the NUDT15 R139C variant was strongly associated with AZA‐induced leukopenia in Chinese patients. The genetic screening of NUDT15 R139C followed by use of alternative immunosuppressants in identified carriers effectively decreased the incidence of AZA leukopenia for patients with autoimmune disorders.